Long-term therapy with cyclosporine and alternate-day prednisone in patients with idiopathic Steroid Resistant Nephrotic Syndrome (SRNS) - Dr Dipti Devi (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: The treatment of SRNS, which comprises 10-20% patients with idiopathic nephrotic syndrome, is difficult. Currently calcineurin inhibitors are recommended as the 1st line drug in idiopathic SRNS. Objective: Studies on cyclosporine are available for SRNS as early as 1980. We report here our long-term experience with Cyclosporine & prednisolone in these patients during those days of early experiences on cyclosporine. Methods: Case records of patients with idiopathic SRNS between 1995 & 2006 were reviewed. Patients who received >6-months treatment with cyclosporine & prednisolone were included. Those with onset in infancy & Schwartz GFR <60 ml/min/1.73m2 were excluded. Response was defined as complete remission, partial remission or non-response. Results: Of 58 patients, 32 had initial and 26 had late resistance. All received therapy with PO steroids. Some received PO/IV cyclophosphamide. The mean (SD) age at presentation & treatment were 60.4 (38) & 75 (43) months. All except one had pretreatment biopsy. Biopsy showed minimal change disease, focal segmented glomerulosclerosis and mesangioproliferative glomerulonephritis in 20, 25 and 12 cases respectively. The mean time to onset of complete remission or partial remission was 3.3 (2.7) months & duration of treatment was 22.4 (14.7) months. Complete remission, partial response, no response & late cyclosporine resistance were seen in 48%, 33%, 12% & 7% patients respectively. Responses were similar in patients with various histologic lesions. Of 18 patients re-biopsied after 2 years of therapy, 3 (16.7%) showed evidence of cyclosporine toxicity, which were mild and manageable. Conclusion: Treatment with cyclosporine and alternate day prednisolone is effective and safe in patients with idiopathic SRNS.